FROM "TRADITIONAL AUTHORITY" TO "DIVERSITY MANAGEMENT": SOME RECENT WRITING ON MANAGING THE WORKFORCE - Maré, Gerhard (PINS-Psychology in Society, 2026)
There lies great danger in the facile use of such generalising terms as "the African worker", "the African village", "the Afrikaner". This applies to everyday life and many other situations; no less so for political practice and social understanding. The employment of such homogenising and essentialising notions often stand in the way of analysis of otherwise complex issues and of appropriate intervention.